Risk and associates of incident hip fracture in type 1 diabetes: The Fremantle Diabetes Study. (December 2017) - Hamilton, Emma J.; Davis, Wendy A.; Bruce, David G.; Davis, Timothy M.E.
Highlights: There have been few studies of hip fracture in type 1 diabetes in the community. We compared hip fracture rates in type 1 patients and controls without diabetes. We also compared hip fracture rates in matched type 1 and type 2 patients. Type 1 diabetes was associated with a substantially increased risk in both cases. Abstract: Aims: To determine the relative risk of incident hip fracture in patients with type 1 diabetes and matched controls, to examine baseline associates of incident hip fracture in the patients with type 1 diabetes, and to compare hip fracture rates in age- and sex-matched patients with type 1 versus type 2 diabetes. Methods: Longitudinal observational study of 121 adults with type 1 diabetes (mean ± SD age 43.0 ± 15.5 years, 59.5% male) and 484 age- and sex-matched adults without diabetes. Age and sex matching was possible for 93 pairs of type 1 and type 2 participants. The main outcome measure was incident hip fracture hospitalisation. Results: During a mean ± SD 14.5 ± 5.8 years of follow-up, the incidence rate ratio for first hip fracture hospitalisation in type 1 participants versus residents without diabetes was 6.39 (95% CI 1.94–22.35, P  < .001). In Cox proportional hazards modelling, type 1 diabetes was associated with cause-specific hazard ratio (csHR) for hip fracture of 7.11 (2.45–20.64, P  < .001) after age and sex adjustment. Hip fracture in type 1 participants was associated with older age, osteoporosis treatment, depressive symptoms, ethnicity, systolic blood pressure, serum HDL-cholesterol, albuminuria and serum adiponectin ( P  ≤ 0.047); associations remained for the first three of these variables after adjustment for age and body mass index ( P  ≤ 0.025). The csHR for incident hip fracture was 5.32 (1.12–25.37, P  = .036) for type 1 versus 2 diabetes. Conclusions: Hip fracture risk is markedly elevated in type 1 diabetes compared with age and sex-matched individuals without diabetes and with type 2 diabetes from the same population.